Autonomic nervous system functions in interictal and postictal periods of nonepileptic psychogenic seizures and its comparison with epileptic seizures - Muengen, Buelent; Berilgen, M. Said; Arikanoglu, Adalet (W B Saunders Co Ltd, 2010)
Purpose: (1) To evaluate autonomic nervous system (ANS) functions during both interictal and postictal periods in a group of cases with nonepileptic psychogenic seizures (NEPS) and a group of epileptic patients to determine whether they have autonomic dysfunction. (2) If a significant difference can be established between epileptic and NEPS groups, to determine whether ANS tests can be used as a clinical helper in the differentiation between epileptic seizures (ES) and NEPS. Methods: ANS functions (sympathetic skin response and R-R interval variation) were measured during both interictal and postictal periods in 25 patients who had NEPS and 30 patients who had primary generalized tonic-clonic seizures (GTCS) and partial seizures with secondary GTCS, as well as once in the healthy control group. Results: When the patient group with NEPS both in the interictal and postictal period was compared with the control group, functions of both sympathetic and parasympathetic systems were found normal. This finding implies that patients with NEPS have normal ANS functions. A comparison of the epileptic patient group in the interictal and postictal periods with the control group revealed that the former had dysfunctions in both the sympathetic and parasympathetic systems. When patients with NEPS were compared with the ES, the measurements in sympathetic and parasympathetic nervous system functions during the interictal and postictal periods in the ES group were significantly different than those of the NEPS group. Conclusion: This finding indicates that measurements of ANS functions may be helpful in differentiating between ES and NEPS. (C) 2010 British Epilepsy Association. Published by Elsevier Ltd. All rights reserved.
Keywords: Autonomic nervous system; Epileptic seizures; Nonepileptic psychogenic seizures